ETHNIC AND CULTURAL IDENTITY OF FRENCH COMMUNICATION BEHAVIOR - M. V. Murieva (Science and Innovation Center Publishing House, 2020)
The article reveals the idea of maintaining the teaching of French language within the national education system as one of the popular European languages along with English language teaching. In order students are able to communicate effectively with native speakers it is critical to learn about ethnic and cultural features of French communication behavior besides attained language skills.